Feminization of Nature: The Portrayal of Woman and Nature in Ronggeng Dukuh Paruk - Laksmitarukmi, Atyaka (Indonesian Journal of English Language Studies (IJELS), 2017)
In Indonesian prose, nature is frequently described as the life support of human beings. The studies about the role of nature in Indonesian prose are still anthropocentric. This paper analyses the position of nature in parallel to woman as the feminine side of culture against male domination using the ecofeminist approach. This paper analyzes Ronggeng Dukuh Paruk by Ahmad Tohari which describes nature as an explorative aspect and culture as a more treasured value than nature. Furthermore, this novel is used to perceive that the work of Asian writers is worth studying as well as to show that the work provides characteristics of the region. By adding another perspective using ecofeminism, this study is expected to contribute in the studies of Asian Literature, especially in Indonesian literature. In addition, this study contributes in the reading of nature exploitation in literary work and discourse about ecofeminism.Â Keywords: nature, ecofeminism, feminization, culture, Asian Literature